Immunological impact of an additional early measles vaccine in Gambian children: responses to a boost at 3 years. - Njie-Jobe, J; Nyamweya, S; Miles, D; van der Sande, M; Zaman, S; Touray, E; Hossin, S; Adetifa, J; Palmero, M; Burl, S; Jeffries, D; Rowland-Jones, S; et al. (2012)
BACKGROUND: Measles vaccine in early infancy followed by a dose at 9 months of age protects against measles and enhances child survival through non-specific effects. Little is known of immune responses in the short or long term after booster doses. METHODS: Infants were randomized to receive measles vaccine at 9 months of age (group 1) or 4 and 9 months of age (group 2). Both groups received a boost at 36 months of age. T-cell effector and memory responses using IFN-γ ELIspot and cytokine assays and antibody titres using a haemagglutination-inhibition assay were compared at various times. RESULTS: Vaccination at 4 months of age elicited antibody and CD4 T-cell mediated immune responses .Two weeks after vaccination at 9 months of age group 2 had much higher antibody titres than group1 infants; cell-mediated effector responses were similar. At 36 months of age group 2 antibody titres exceeded protective levels but were 4-fold lower than group 1; effector and cytokine responses were similar. Re-vaccination resulted in similar rapid and high antibody titres in both groups (median 512); cellular immunity changed little. At 48 months of age group 2 antibody concentrations remained well above protective levels though 2-fold lower than group 1; T-cell memory was readily detectable and similar in both groups. CONCLUSIONS: An additional early measles vaccine given to children at 4 months of age induced a predominant CD4 T-cell response at 9 months and rapid development of high antibody concentrations after booster doses. However, antibody decayed faster in these children than in the group given primary vaccination at 9 months of age. Cellular responses after 9 months were generally insignificantly different.